Comparison of the Agronomic, Cytological, Grain Protein Characteristics, as Well as Transcriptomic Profile of Two Wheat Lines Derived From Wild Emmer - Gong, Fangyi; Qi, Tiangang; Zhang, Tian; Lu, Yusen; Liu, Jia; Zhong, Xiaoying; He, Jingshu; Li, Yunfang; Zheng, Youliang; Liu, Dengcai; Huang, Lin; Wu, Bihua (Frontiers in Genetics, 2022)
Two advanced wheat lines BAd7-209 and BAd23-1 without the functional gene GPC-B1 were obtained from a cross between common wheat cultivar Chuannong 16 (CN16) and wild emmer wheat accession D97 (D97). BAd7-209 showed superior quality parameters than those of BAd23-1 and CN16. We found that the components of glutenins and gliadins in BAd7-209 and BAd23-1 were similar, whereas BAd7-209 had higher amount of glutenins and gliadins than those of BAd23-1. RNA sequencing analysis on developing grains of BAd7-209 and BAd23-1 as well as their parents revealed 382 differentially expressed genes (DEGs) between the high–grain protein content (GPC) (D97 + BAd7-209) and the low-GPC (CN16 + BAd23-1) groups. DEGs were mainly associated with transcriptional regulation of the storage protein genes, protein processing in endoplasmic reticulum, and protein export pathways. The upregulated gluten genes and transcription factors (e.g., NAC, MYB, and bZIP) may contribute to the high GPC in BAd7-209. Our results provide insights into the potential regulation pathways underlying wheat grain protein accumulation and contribute to make use of wild emmer for wheat quality improvement.